Detection of Novel Reassortant Influenza A (H3N2) and H1N1 2009 Pandemic Viruses in Swine in Hanoi, Vietnam. (1st November 2014) - Baudon, E.; Poon, L. L.; Dao, T. D.; Pham, N. T.; Cowling, B. J.; Peyre, M.; Nguyen, K. V.; Peiris, M.
Summary From May to September 2013, monthly samples were collected from swine in a Vietnamese slaughterhouse for influenza virus isolation and serological testing. A(H1N1)pdm09 viruses and a novel H3N2 originating from reassortment between A(H1N1)pdm09 and novel viruses of the North American triple reassortant lineage were isolated. Serological results showed low seroprevalence for the novel H3N2 virus and higher seroprevalence for A(H1N1)pdm09 viruses. In addition, serology suggested that other swine influenza viruses are also circulating in Vietnamese swine.